The potential of induced pluripotent stem cells as a tool to study skeletal dysplasias and cartilage-related pathologic conditions. Issue 5 (May 2017) - Liu, H.; Yang, L.; Yu, F.F.; Wang, S.; Wu, C.; Qu, C.; Lammi, M.J.; Guo, X.
Summary: The development of induced pluripotent stem cells (iPSCs) technology has opened up new horizons for development of new research tools especially for skeletal dysplasias, which often lack human disease models. Regenerative medicine and tissue engineering could be the next areas to benefit from refinement of iPSC methods to repair focal cartilage defects, while applications for osteoarthritis (OA) and drug screening have evolved rather slowly. Although the advances in iPSC research of skeletal dysplasias and repair of focal cartilage lesions are not directly relevant to OA, they can be considered to pave the way to future prospects and solutions to OA research, too. The same problems which face the present cell-based treatments of cartilage injuries concern also the iPSC-based ones. However, established iPSC lines, which have no genomic aberrations and which efficiently differentiate into extracellular matrix secreting chondrocytes, could be an invaluable cell source for cell transplantations in the future. The safety issues concerning the recipient risks of teratoma formation and immune response still have to be solved before the potential use of iPSCs in cartilage repair of focal cartilage defects and OA.